Minimally invasive open nephrectomy on children with multicystic dysplastic kidney - Feng, Dongchuan (Exp Ther Med, 2016)
The aim of the study was to summarize the preliminary experience of minimally invasive open nephrectomy operation on children with multicystic dysplastic kidney (MCDK). A retrospective review was performed on the clinical materials of the 15 children that had accepted consecutive minimally invasive open nephrectomies during the previous 2 years. The enrolled children were diagnosed with unilateral MCDK under computed tomography, emission computerized tomography and ultrasound and no anomaly in the contralateral functioning kidney was found. Of the 15 children, 12 were boys and 3 were girls, with 5 cases on the right and 10 cases on the left. Operations were completed at the retroperitoneal space in order to open an incision on the waists and ribs of the children, the length of which ranged from 1.5 to 2.0 cm (average 1.7 cm). The age of the children at operation ranged from 3 months to 5.6 years old, with an average of 2.4 years old. Surgery lasted for 30–50 min, with an average of 34.6 min. The estimated blood loss of each child was <5 ml. After operation, prophylactic intravenous antibiotics were administered for 2–4 days to prevent infection. All of the operations proved very successful. Following surgery the children were hospitalized for 2–4 days for observation, with an average of 2.8 days. No complications occurred during the follow-up period. In conclusion, minimally invasive open nephrectomy is effective for children with MCDK. The procedure is superior with regard to operative time, cosmesis, and length of stay. It is a safe and effective treatment choice for patietns with MCDK and can be easily performed on children.